126k views
0 votes
Write the expression as a single natural logarithm.
3lnm+4lnn

User Skatox
by
5.2k points

1 Answer

10 votes

Answer:

We conclude that:


3\ln \left(m\right)+4\ln \left(n\right)=\ln \left(m^3n^4\right)

Explanation:

Given the expression


3\ln \left(m\right)+4\ln \left(n\right)

Apply log rule:


  • a\log _c\left(b\right)=\log _c\left(b^a\right)

So the expression becomes


3ln\:m\:+\:4ln\:n=\ln \:\left(m^3\right)+\ln \:\left(n^4\right)

Apply log rule:


\log _c\left(a\right)+\log _c\left(b\right)=\log _c\left(ab\right)

so the expression becomes


=\ln \left(m^3n^4\right)

Therefore, we conclude that:


3\ln \left(m\right)+4\ln \left(n\right)=\ln \left(m^3n^4\right)

User Brokenbeatnik
by
5.5k points